(untitled) (Research, Society and Development, 2021)
Talking about the subject of death is challenging. If for adults it is something very mysterious, imagine talking about this subject for children, because, due to their level of maturity and affective and emotional development, they are not prepared to understand such a quote. This research aimed to understand the different emotional reactions to grief in childhood through children’s literature. Therefore, a qualitative literary narrative review and a detailed analysis of scientific publications that address the subject were carried out. In general, frank and clear dialogue is recommended, through true and honest information, promoting the insertion and construction of the concept of death, as something natural, from early childhood, with a communicator open to clarifying doubts and sensitive listening, which favors the expression of the different feelings that affect a child in this situation. This interaction must be covered by some strategies and basic care, respecting the child’s cognitive and emotional abilities.